Small molecules containing rigidified thiophenes and a cyanopyridone acceptor unit for solution-processable bulk-heterojunction solar cells. (August 2015) - Gupta, Akhil; Ali, Abdelselam; Gao, Mei; Singh, Th. Birendra; Bilic, Ante; Watkins, Scott E.; Bach, Udo; Evans, Richard A.
Abstract: We designed two solution processable small molecules, 5-((5-(4-(diphenylamino)phenyl)thieno[3, 2- b ]thiophene-2-yl)methylene)-1-(2-ethylhexyl)-4-methyl-2, 6-dioxo-1, 2, 5, 6-tetrahydropyridine-3-carbonitrile (1 ) and 5-((6-(4-(diphenylamino)phenyl)-4-(2-ethylhexyl)-4 H -dithieno[3, 2- b :2′, 3′-d]pyrrol-2-yl)methylene)-1-(2-ethylhexyl)-4-methyl-2, 6-dioxo-1, 2, 5, 6-tetrahydropyridine-3-carbonitrile (2 ), consisting of a triphenylamine electron donating group and a cyanopyridone electron accepting group linked by two different rigidified π-spacer thiophenes. Ultraviolet–visible absorption spectra revealed that the use of three fused rings (dithienopyrrole) as the conjugated π-spacer resulted in an enhanced intramolecular charge transfer transition and reduction of band gap, when compared with a non-fused bithiophene and two fused thiophenes (thienothiophene) analogues. Power conversion efficiencies (PCEs) of 2.39% and 2.14% were achieved for simple photovoltaic devices based on1 /PC61 BM and2 /PC61 BM under simulated AM 1.5 illumination (100 mW cm −2 ), respectively. It has been observed that the degree of conjugation of the central π-bridge was not a key factor for the enhancement of photovoltaic performance. Graphical abstract: Highlights: Use of rigidified thiophenes in conjunction with aromatizable cyanopyridone acceptor. Linkage of rigidified thiophenes to aromatizable acceptor for spectral red-shift. Two fused thiophenes display better film morphology comparing to three fused heterocycles incorporating thiophenes.